VO₂ Max Levels of Sepak Takraw Athletes at Muhammadiyah University of Education Sorong - Wahyu Retno Widiyaningsih; Waskito Aji Suryo Putro; Sugiono; Istiyono; Hendriawan Prasetyo; Afifah Aulia Putri Arisma; Mohansundar Sankaravel (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This study aimed to determine the VO₂max level of sepak takraw athletes. The findings are expected to provide valuable information for athletes and coaches in evaluating cardiorespiratory endurance as a basis for designing appropriate training programs and improving athletic performance during both training and competition. This study employed a quantitative descriptive research design using a survey method with a multistage fitness test (beep test) to estimate the athletes' VO₂max. The participants consisted of 13 sepak takraw athletes. The results showed that 1 athlete (6%) was classified in the very good category, 7 athletes (67%) were in the good category, and 5 athletes (28%) were in the moderate category. The mean estimated VO₂max score was 45.6 mL·kg⁻¹·min⁻¹, indicating that the overall cardiorespiratory fitness level of the athletes was in the good category. Maintaining an adequate VO₂max is essential for sepak takraw players to sustain training intensity, optimize competitive performance, and minimize physical fatigue during matches.